On Decompositions of Continuity and Complete Continuity in Ideal Topological Spaces (European Journal of Pure and Applied Mathematics, 2017)
We define new classes of sets called I-open set, ô€€€ I-open set, ô€€€ Iô€€€set, semi ô€€€ Iopen set, sI ô€€€ g-closed set in ideal topological spaces. Using these sets, we obtain decompositions of continuity and complete continuity in ideal topological spaces. Also, we investigate some properties ofthese sets and relationship other generalized sets.